Penambahan Berat Badan Ibu Selama Hamil Dengan Berat Badan Lahir Bayi Di UPT Puskesmas Dlanggu Kabupaten Mojokerto - Zulfa Rufaida; Sri Wardini Puji Lestari; Ika Yuni Susanti (Jurnal Kesehatan Masyarakat Mulawarman (JKMM), 2020)
Women weight before pregnancy and weight gain during pregnancy are the main determinants of the baby's weight at the end. Women with low body weight (for example <55 kg) before pregnancy who achieved a slight increase in body weight (<4500 grams) during pregnancy had a higher incidence of giving birth to babies with low birth weight than mothers with greater weight who reached more a lot of weight gain during pregnancy (Benson, 2009: 135). The purpose of this study was to determine women weight gain during pregnancy with birth weight.This research design uses "Cross Sectional". The independent variable is the weight of pregnant women and the dependent variable is the weight of the newborn. The population in this study were all mothers with babies at birth in UPT Puskesmas Dlanggu, Mojokerto Regency. A sample of 50 respondents was taken using consecutive sampling techniques. Data analysis used fisher exact test with α = 0.05.The results showed that most pregnant women gained weight in the normal category of 36 people (72.0%). The majority of babies born underweight did not experience underweight, namely 42 people (84.0%). Fisher exact test results = 0.004 <0.05 so that H1 is accepted and H0 is rejected, which means there is a relationship between maternal weight gain during pregnancy and the baby's birth weight at UPT Puskesmas Dlanggu, Mojokerto Regency.Women weight / before pregnancy and weight gain of pregnant women need to get attention because there is a clear relationship with the weight and development of the fetus in the uterus. Health workers should always provide education about nutritional needs during pregnancy and also monitor the development of pregnant women and the fetus so that immediate action can be taken if found abnormalities in pregnancy.Keywords: Increase in Maternal Weight During Pregnancy, Baby Birth Weight